2010
DOI: 10.1364/ol.35.000396
|View full text |Cite
|
Sign up to set email alerts
|

Order-of-magnitude polymerization-shrinkage suppression of volume gratings recorded in nanoparticle-polymer composites

Abstract: We demonstrate substantial shrinkage suppression of nanoparticle-polymer composite transmission gratings by use of the step-growth polymerization mechanism. It is shown that the polymerization shrinkage can be reduced as low as 0.3% at the nanoparticle concentration of 35 vol. % by which the refractive index modulation and the material sensitivity are maximized to be 8x10(-3) and 1014 cm/J, respectively, in the green. Our results offer a noticeable advance in the development of holographic data storage materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 16 publications
1
44
0
2
Order By: Relevance
“…These values were within the acceptable range of values for holographic data storage media (i.e., Δn sat = 5 × 10 −3 , S = 500 cm 2 /J and 0.5% shrinkage). It was also shown that because of the dispersion of the inorganic silica nanoparticles and the use of the triene monomer, (having the rigid structure of the triazine functional group), the thermal stability of the recorded holograms is much improved compared to that of those previously reported in earlier nanoparticle-polymer composites using organic nanoparticles and primary mercaptopropionate trithiol/allyl ether triene monomers [53,78].…”
Section: Physics Research Internationalmentioning
confidence: 91%
See 1 more Smart Citation
“…These values were within the acceptable range of values for holographic data storage media (i.e., Δn sat = 5 × 10 −3 , S = 500 cm 2 /J and 0.5% shrinkage). It was also shown that because of the dispersion of the inorganic silica nanoparticles and the use of the triene monomer, (having the rigid structure of the triazine functional group), the thermal stability of the recorded holograms is much improved compared to that of those previously reported in earlier nanoparticle-polymer composites using organic nanoparticles and primary mercaptopropionate trithiol/allyl ether triene monomers [53,78].…”
Section: Physics Research Internationalmentioning
confidence: 91%
“…Later in that year, Hata and Tomita [78] proposed a novel nanoparticle-polymer composite to further suppress shrinkage of their material using of the thiol-ene step-growth polymerization mechanism. Due to crosslinked thiol-ene, polymerisation proceeds very rapidly but will not reach the gel point until high functional group conversions take place, that is, reaching the gelation point later during conversion in the mixtures accelerates the mutual diffusion and phase separation of the monomer molecules and nanoparticles during recording.…”
Section: Physics Research Internationalmentioning
confidence: 99%
“…Indeed, we adopted these polymerization mechanisms for NPCs and demonstrated substantive shrinkage mitigation. [25][26][27][28] In particular, we showed excellent performance of volume holographic recording in NPCs using thiol-ene monomers 29,30 that possess the step-growth polymerization mechanism with which gelation occurs late in conversion since the molecular weight increases throughout the course of the reaction. Shrinkage occurring before and during gelation can be readily accommodated by the liquid mixture of oligomers since high-molecular-weight polymer is not obtained until the end of the polymerization.…”
Section: Introductionmentioning
confidence: 92%
“…During photopolymerization, volume shrinkage is inevitable and thereby holographically formed grating is distorted and finally, the diffraction efficiency is deteriorated [12]. In order to overcome volume shrinkage issue, various photopolymer systems including nanoparticles-dispersed photopolymer composites, nanoporous glasses photopolymer composites, cationic ring opening system, and epoxy-based two chemistry formulations, have shown some promising results [13][14][15][16][17][18][19][20]. However, each system has drawbacks associated with shelf-life stability.…”
Section: Introductionmentioning
confidence: 99%